The Measurement of Information Quality and E-Service Quality on Customer Satisfaction in Shopee Indonesia - Maria Wirani; Anggalia Wibasuri (Proceeding International Conference on Information Technology and Business, 2020)
E-Commerce changes consumer behavior in shopping from buying in physical places to buying through online media. During the Covid 19 pandemic in Indonesia. Online shopping activities is increased by 400 percent. The high percentage growth in the number of Shopee Marketplace visits compared to other Marketplaces during the Covid 19 pandemic period Q1 - Q3 2020 indicates consumer satisfaction shopping online at the Shopee marketplace. The purpose of this study was to determine the effect of information quality and e-service quality on customer satisfaction in Shopee Indonesia. The sampling method in this study used non-probability sampling using the purposive sampling technique with a sample size of 150 respondents. Data analysis in this study using Multiple Linear Regression.Keywords: Information Quality, E-Service Quality, Customer Satisfaction.